Terra seca, homem seco : as relações entre a literatura e o ensino da Geografia - Velasco, Patrícia (2012)
This essay had the goal to analyse the relation between man/nature through the masterpiece Vidas Secas , by Graciliano Ramos, giving emphasis to the influence of the space of life and strength of nordestino scenery in the spirit, attitude and behavior of his characters. For this, it was necessary to define the historic context in which the masterpiece was made to understand the representations of the power that reach the characters in a reference to the dictatorial period of Estado Novo , ruled by Getúlio Vargas. In it, the vision of the northern region is of a dry region, poor and far from the center of the power decision. The drought of the human beings, of few words, always humiliated is portrayed in this story told by a third person. Fabiano, in the cowboy character, nomad jew, search for a mid-place , who is not in his hometown ( the inward of sertão), or in the one that is coming (the city), but in a huge need of survival, of being recognized as a man and not as a beast-man. From a personal reading of the novel Vidas Secas , enriched with the propositions of Antonio Candido, Lino Macedo, Nicolau Sevencko, Carlos Augusto Figueiredo Monteiro e Rui Moreira we looked for enlarging the dialog between Literature and Geography, as a contribuition to the basic teaching of these curricular components. We looked for, however, an analyse of the literary and geographic space in the masterpiece itself, as the own expression of the real lived and not only an imaginary description, a transformation of the reality into fiction